PENGARUH PERCEIVED USEFULNESS DAN PERCEIVED EASE OF USE TERHADAP ACTUAL USAGE MELALUI ATTITUDE TOWARD USING DALAM DIGITALISASI SISTEM PERPAJAKAN UMKM - Husna, Nur Lailatul; Cahyaningsih, Diyah Sukanti; Kumar, Abdul Malik (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2025)
This study aims to analyze the influence of perceived usefulness and perceived ease of use on actual usage through attitude toward using in the adoption of Digitalzation of Tax Administration System by MSMEs, using the Technology Acceptance Model (TAM) approach. The research was conducted on MSME actors in Semarang City, using a random sampling technique with a total of 206 respondents. Data were collected through online questionnaires distributed via Google Forms and analyzed using the Structural Equation Modeling Partial Least Square (SEM-PLS) method with the SmartPLS 4.0 software. The results show that perceived usefulness and perceived ease of use have a positive effect on attitude toward using. Furthermore, perceived usefulness and attitude toward using have a significant positive effect on actual use, while perceived ease of use does not significantly affect actual use. However, both perceived usefulness and perceived ease of use positively influence actual use through the mediating role of attitude toward using.The implications of this study highlight the importance of the role of government and academics in providing guidance and assistance to MSME actors in optimizing the use of digital tax administration systems based on the Technology Acceptance Model approach.Keywords: Attitude Toward Using, Actual Usage, Digital Tax Administration System, Perceived Usefulness, Perceived Ease of Use TAM, MSMEs